2017
DOI: 10.1177/1941738117729660
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Reoperation and Performance-Based Outcomes After Operative Fixation of Foot Fractures in the Professional Athlete: A Cross-Sport Analysis

Abstract: Background:Professional athletes are predisposed to fractures of the foot due to large stresses placed on the lower extremity. These players are concerned with efficiently returning to play at a high level. Return-to-play rates after operative treatment have been previously reported, yet performance outcomes after such treatment are generally unknown in this population.Hypothesis:Overall, professional athletes sustaining a foot fracture would return to play at high rates with little impact on postoperative per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Four studies were categorized into stress injuries and fractures of the foot/ankle. 5 , 26 , 42 , 49 Khan et al 26 evaluated bony stress injuries in the lower extremity between 2005 and 2015, and 76.1% of these occurred in the foot or ankle. Stress reactions had a 13% progression rate to fracture, and those with stress injuries had a significant decline in number of games played after injury (2 years before vs 2 years after, 72.0 ± 12.7 vs 61.3 ± 20.2, respectively; P = .014).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were categorized into stress injuries and fractures of the foot/ankle. 5 , 26 , 42 , 49 Khan et al 26 evaluated bony stress injuries in the lower extremity between 2005 and 2015, and 76.1% of these occurred in the foot or ankle. Stress reactions had a 13% progression rate to fracture, and those with stress injuries had a significant decline in number of games played after injury (2 years before vs 2 years after, 72.0 ± 12.7 vs 61.3 ± 20.2, respectively; P = .014).…”
Section: Resultsmentioning
confidence: 99%
“…22,69,76,116,140 There was a nonsignificant association with player availability in 1 study 22 and no association in another, 140 as well as a negative effect on performance. 131 Successful completion of at least 1 college season after surgery for fifth metatarsal fracture decreased the likelihood of reinjury. 117 Operative treatment was successful at maximizing RTP when it employed (1) a protocol of fixation with a Jones-specific intramedullary screw and iliac crest bone marrow aspirate with demineralized bone matrix injected at the fracture site, (2) noninvasive bone stimulators, (3) use of customized orthoses, and (4) an aggressive patient-specific rehabilitation protocol; however, 12% developed nonunion and required revision surgery when returning during the same season (at a mean of 9 weeks).…”
Section: Resultsmentioning
confidence: 99%
“…Citing a lack of outcomes in the literature regarding elite athletes undergoing operative management of foot fractures, Singh et al investigated RTP rates and postoperative performance in NBA, NFL, MLB, and NHL players. 47 Of the 84 operative procedures, 3 occurred in NHL players. NHL players had first metatarsal fractures and a navicular fracture.…”
Section: Resultsmentioning
confidence: 99%
“…NHL players were omitted from the performance analysis due to the small sample size, and the authors concluded that overall, athletes had excellent postoperative outcomes with a RTP of 98.7% regardless of sport and fracture location. 47…”
Section: Footmentioning
confidence: 99%